Identification Of The Predominant Oral Microbiome In Pericoronitis - Ainaa Liyana Azemi; Azmiza Syawani Jasni; Siti Noor Adnalizawati Adnan; Rohazila Mohamad Hanafiah; John Chong Keat Hon; Ahmad Dzulfikar Samsuddin (Journal of International Dental and Medical Resear, 2024)
Journal of International Dental and Medical Research ISSN1309-100X http://www.jidmr.com Volume ∙12∙ Number∙4∙ 2019